Isu Syiah Sesat di Universitas Islam Negeri Raden Fatah Palembang; Studi Atas Pandangan Akademisi Dalam Upaya Deradikalisasi Faham Keagamaan - Noupal, Muhammad (Medina-te : Jurnal Studi Islam, 2022)
The background to this article is due to the issue of heretical sects against Shia teachings in the view of lecturers or academics at Islamic Religious Colleges (PTKI), including at Raden Fatah State Islamic University (UIN) Palembang. It is feared that the issue of heretical sects will lead to intolerance and radical thinking, such as making statements "infidel" or "heretical" to fellow Muslims. The purpose of this study is to get an overview from academics at UIN Raden Fatah about their views on Shia ideology or sects and to relate it to efforts to deradicalize religious views among the dpsen. The type of this research is a qualitative research. The results of this study indicate that as an academic, the views of UIN Raden Fatah lecturers do not see that all Shia teachings are heretical; except Shia Hullat who are extreme. They even agree that Shia teachings are studied scientifically either in class or in an open discussion to gain an objective and balanced understanding.